Athletic pseudonephritis in male cross-country ultra-marathoners: a comparative observational study - Chen, Kai-Hung; Lee, Cheng-Hsun; Chen, Pang-Yen; Li, Li-Hua; How, Chorng-Kuang; Lin, Yen-Kuang; Chiu, Yu-Hui; Wang, Feng-Lin; Kao, Wei-Fong; Huang, Ming-Kun; Chien, Ding-Kuo; Chang, Wen-Han (Frontiers in Physiology, 2025)
Background/ObjectiveAthletes have commonly reported hematuria, cylindruria, and proteinuria, which are consistent with “athletic pseudonephritis.” To date, little is known about the overall consequences of 100 km (62.5-mile) cross-country ultra-marathons on Asian male runners. This study aimed to examine (i) acute urinary changes in runners with athletic pseudonephritis following a 100 km cross-country ultra-marathon and (ii) whether this phenomenon is associated with the runners average running speed.MethodsTwenty male Taiwanese ultra-marathoners were prospectively recruited. Urinary parameters were analyzed before and immediately after the 2020 Taiwania 100 K Ultra Trail. Competitors ran on a rugged forest path and the official cut-off time was 15 h.ResultsParticipants showed a statistically significant post-race increase (p < 0.001) in urinary red blood cell counts. No significant difference was noted in urinary cast in the immediate post-race values compared to the pre-race values (p = 0.488). Urinary chemistry showed statistically significant increases in specific gravity (p < 0.001), osmolality (p < 0.001), creatinine (p = 0.027), microalbumin (p < 0.001), protein (p < 0.001), and myoglobin (p < 0.001) between the pre- and post-race values. Additionally, 10 (50%) post-race specimens had albumin-to-creatinine ratios >30 mg/g, and 9 (45%) specimens showed protein-to-creatinine ratios >0.2 mg/mg. The association between running speed and red blood cells in urine showed a p-value of 0.368. There were no correlations between running speed and changes in albumin-to-creatinine ratio (rs = −0.105, p = 0.661), protein-to-creatinine ratio (rs = −0.013, p = 0.957), or myoglobin (rs = 0.003, p = 0.99) levels.ConclusionExercise-related hematuria and proteinuria were frequently observed in the Asian male cross-country ultra-marathoners. A faster running speed was not associated with the degree of exercise-induced hematuria, proteinuria or myoglobinuria.